Heterogeneity of sensory features in autism spectrum disorder: Challenges and perspectives for future research. Issue 5 (7th March 2017) - Uljarević, Mirko; Baranek, Grace; Vivanti, Giacomo; Hedley, Darren; Hudry, Kristelle; Lane, Alison
Abstract : Pronounced heterogeneity is apparent across every facet of autism spectrum disorder (ASD) and it remains difficult to predict likely future potential among individuals who share a common diagnosis of ASD on the basis of early presentation. In this commentary we argue that a fine‐grained understanding of individual differences in sensory features and their influence across the life span can constrain noted clinical heterogeneity in ASD. We organize our discussion around the following three critical themes: (a) considering sensory features as dimensional construct; (b) taking an "individual differences" approach; and (c) adopting a comprehensive, multidimensional and multimodal approach to measurement of sensory features. We conclude that future research will need to investigate individual differences in sensory features via: (1) multidimensional and cross‐disciplinary examination, (2) prospective longitudinal designs, and (3) dimensional and developmental frameworks that emphasize the potential value of early individual variability as indicators of later outcomes, not only in relation to the categorical diagnostic outcome status but also the presence of other clinical features. This is a key time for sensory‐related research and in this commentary we provide some of the steps that, in our opinion, can shape future research in this area. Autism Res 2017, 10: 703–710 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.